Biodegradation Potential of Streptomyces sp. Against propineb-Based 70% Fungicide Under In Vitro Conditions - Sari, Nadya Naurah; Mujoko, Tri; Wiyatiningsih, Sri (CROPSAVER, 2025)
The intensive use of propineb-based fungicides in agriculture can negatively affect the environment due to toxic and persistent residues in soil. An environmentally friendly approach to reduce these impacts is bioremediation using microorganisms such as Streptomyces sp. This study aimed to examine the tolerance and biodegradation potential of Streptomyces sp. toward 70% propineb fungicide under in vitro conditions. The research was conducted at the Plant Health 1 Laboratory, Universitas Pembangunan Nasional “Veteran” East Java, from June to August 2025. The experiments were carried out in two stages: (1) a tolerance assay on Glucose Nutrient Agar containing propineb at 0; 0,50; 1,00; 1,50; and 2,00 g/L, and (2) a degradation assay using a dual-culture method with Colletotrichum sp. as a bioindicator. Observation variables included Total Plate Count (TPC) of Streptomyces sp., colony diameter of Colletotrichum sp., and the relative inhibition level (THR). Results showed that Streptomyces sp. was able to grow at all fungicide concentrations. The highest population was found in P0 (0 g/L) with 1,42×1013 CFU/mL with growth decreasing as propineb concentration increased, reaching the lowest level of 3,22×10¹⁰ CFU/mL in P4 (2.00 g/L). In the degradation assay, Colletotrichum sp. colony diameter decreased from 3,38 cm in P0 (0 g/L)  to 2,24 cm in P4 (2,00 g/L). Meanwhile, THR values increased consistently with fungicide concentration, rising from 3,17% in P0 (0 g/L)  to 35,48% in P4 (2,00 g/L).